2017
DOI: 10.5301/jsrd.5000247
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension screening of systemic sclerosis patients in clinical practice: an independent chart review

Abstract: 78% and 47%, respectively. Those with underlying pulmonary fibrosis have even worse survival rates (3). Screening for PAH in SSc leads to earlier diagnosis, implementation of appropriate therapy, and improvement of clinical outcomes (5). To improve early detection of PAH, several organizations have published guidelines recommending annual screening for dyspnea and either pulmonary function testing (PFT), transthoracic echocardiogram (TTE), or both, starting at the time of SSc diagnosis (6-8). A combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The response rate of 16.8% is similar to previous studies on this topic. 11 This study shows that while screening rates continue to be sub-optimal (81% for TTE and 78% for PFT), rates were similar to those in Hamilton, Ontario 8 and slightly higher than Canadian SSc specialists in 2012. 9 Interestingly, screenings rates reported here are also higher than those seen in Australia which ranged from 40 to 60% depending on the type of SSc (limited vs. diffuse) and duration of disease.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The response rate of 16.8% is similar to previous studies on this topic. 11 This study shows that while screening rates continue to be sub-optimal (81% for TTE and 78% for PFT), rates were similar to those in Hamilton, Ontario 8 and slightly higher than Canadian SSc specialists in 2012. 9 Interestingly, screenings rates reported here are also higher than those seen in Australia which ranged from 40 to 60% depending on the type of SSc (limited vs. diffuse) and duration of disease.…”
Section: Discussionmentioning
confidence: 74%
“…• • Initial screening of all patients with pulmonary function testing (PFT) including diffusing capacity for carbon monoxide (DLCO), transthoracic echocardiogram (TTE) and N-terminal pro b-type natriuretic peptide (NT-Pro BNP); Annual PFT and TTE, even in asymptomatic patients Previous research has examined local rheumatologists' screening practices within Hamilton, Ontario 8 and among SSc specialists across Canada. 9 Kelly et al 8 found that Hamilton rheumatologists who self-identified as SSc experts were more likely to order annual screening TTEs and PFTs than non-experts. In contrast, a Canada-wide study found no significant difference in screening rates between experts and a select group of seven non-experts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation